The Social Context of 4QInstruction Reconsidered: Wisdom, Inheritance and Priesthood in 4Q418 frg. 81 - Shirav, Annah (Dead Sea discoveries, 2022)
The nature and the social context of Instruction were often discussed in the scholarship. Its relatively high number of copies that have been found in Qumran, and a series of shared literary, linguistic and ideological similarities to compositions often closely associated with the Qumran movement led scholars to debate the attribution of Instruction to this group of texts. This paper argues that the pericope in 4Q418 frg. 81, which uses extensively priestly language and metaphors, reflects similar social context and structure as the Community Rule, and therefore Instruction should be placed among the writings of the community. I will use two-stage analysis of the pericope, which will offer insight on the identity of the addressee, and try to bring some fresh insights on the literary unity of the composition.